2015
DOI: 10.14737/journal.aavs/2015/3.4.207.210
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Profile of Goats Subjected to Oestrus Synchronization and its Relevance in Predicting Pregnancy Outcome

Abstract: | Successful oestrous synchronization protocol must support a reasonable level of pregnancy in the synchronized cycle. Premature luteal regression and a drop in progesterone, the pregnancy hormone and concentration is a common phenomenon in goats following oestrus synchronization. Therefore, this study was undertaken to evaluate the comparative efficacy of two oestrus synchronization protocols on the progesterone profile of the Malabari cross bred goats which would be of practical significance for estrous sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Also, a correlation was observed between the oestrus intensity and the conception rate in goats. In another study by Panicker et al 22 it was observed that the serum progesterone concentrations in prolific Malabari cross-bred goats on the day of insemination showed significant difference (P<0.05) between the goats those conceived and the ones that failed to conceive, with a significantly lower progesterone level in the conceived group.…”
Section: Hormonal Factorsmentioning
confidence: 91%
“…Also, a correlation was observed between the oestrus intensity and the conception rate in goats. In another study by Panicker et al 22 it was observed that the serum progesterone concentrations in prolific Malabari cross-bred goats on the day of insemination showed significant difference (P<0.05) between the goats those conceived and the ones that failed to conceive, with a significantly lower progesterone level in the conceived group.…”
Section: Hormonal Factorsmentioning
confidence: 91%